Mouse Lung Structure and Function after Long-Term Exposure to an Atmospheric Carbon Dioxide Level Predicted by Climate Change Modeling - Larcombe, Alexander N.; Papini, Melissa G.; Chivers, Emily K.; Berry, Luke J.; Lucas, Robyn M.; Wyrwoll, Caitlin S. (Environmental health perspectives, 2021)
Climate change models predict that atmospheric carbon dioxide [ ] levels will be between 700 and 900 ppm within the next 80 y. Despite this, the direct physiological effects of exposure to slightly elevated atmospheric (as compared with experienced today), especially when exposures extend from preconception to adulthood, have not been thoroughly studied. In this study we aimed to assess the respiratory structure and function effects of long-term exposure to from preconception to adulthood using a mouse model. We exposed mice to ( ) from prepregnancy, through the and early life periods, until 3 months of age, at which point we assessed respiratory function using the forced oscillation technique, and lung structure. exposure resulted in a range of respiratory impairments, particularly in female mice, including higher tissue elastance, longer chord length, and lower lung compliance. Importantly, we also assessed the lung function of the dams that gave birth to our experimental subjects. Even though these mice had been exposed to the same level of increased for a similar amount of time ( ), we measured no impairments in lung function. This suggests that the early life period, when lungs are undergoing rapid growth and development, is particularly sensitive to . To the best of our knowledge, this study, for the first time, shows that long-term exposure to environmentally relevant levels of can impact respiratory function in the mouse. https://doi.org/10.1289/EHP7305.